2016
DOI: 10.3928/1081597x-20160629-02
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Iontophoresis Versus Standard Corneal Collagen Cross-linking: 1-Year Results of a Prospective Clinical Study

Abstract: The 1-year outcomes suggest that I-CXL might be comparable to S-CXL in stabilizing the progression of the degenerative ectatic disease. Additionally, quicker improvement of functional parameters was reported in the I-CXL group. [J Refract Surg. 2016;32(10):672-678.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 24 publications
3
47
1
Order By: Relevance
“…The results are consistent with those reported by other studies, noting that our patients are followed up for a longer period of time (Bikbova & Bikbov ; Vinciguerra et al. ; Jouve et al. ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are consistent with those reported by other studies, noting that our patients are followed up for a longer period of time (Bikbova & Bikbov ; Vinciguerra et al. ; Jouve et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…Recent clinical trials have shown that I ‐CXL is a valid method to halt the progression of keratoconus with an improvement of clinical and paraclinical parameters, but with a lower efficacy compared to standard cross‐linking (Bikbova & Bikbov ; Vinciguerra et al. ; Jouve et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the prevalent role of epithelium regrowth in the changes seen post-CXL is substantiated by the fact that the effects of transepithelial (epi on) CXL appear to be less pronounced than the effects of CXL with de-epithelialization (epi off) as described in the literature. 46,[48][49][50] It should be reasonable to conclude, therefore, that the variation in keratometric readings and visual quality observed after CXL may be non-biomechanical and instead be related to epithelial remodeling. We have conducted a study to further investigate the role of the corneal epithelium on the topography of the anterior surface of the cornea.…”
Section: Could Epithelial Wound Healing Account For Most Of the Changmentioning
confidence: 99%
“…[14][15][16][17][18] To counteract this effect, it was proposed that corneal refractive surgery can be combined with corneal cross-linking (CXL), also labelled as "Xtra." [23][24][25][26] The purpose of this paper is to review the published results and findings on the indications, protocols and clinical outcomes of combined refractive surgery and CXL. [19][20][21][22] The surgery is expected to slow down or stop the progression of corneal ectasia.…”
Section: Introductionmentioning
confidence: 99%
“…There are standard, accelerated and pulsed protocols of CXL. [23][24][25][26] The purpose of this paper is to review the published results and findings on the indications, protocols and clinical outcomes of combined refractive surgery and CXL.…”
Section: Introductionmentioning
confidence: 99%